The Association of Breastfeeding and Multiple Sclerosis: Does Formula have any other Risks? - Hajibagher Naeeni, Rozita; Soltanzadeh, Akbar; Nafissi, Shahriar; Yadegari, Samira; Esfahani, Fatemeh; Mohammadi, Mahsa (Archives of Advances in Biosciences, 2024)
Introduction: Multiple sclerosis (MS) is a complex autoimmune disorder of the central nervous system that affects millions of individuals worldwide. While the etiology of MS remains multifactorial and incompletely understood, emerging evidence suggests that various environmental and lifestyle factors may influence its onset and progression. Among these factors, breastfeeding has gained attention as a potential protective mechanism against the development of MS. However, it is unclear whether breastfeeding, colostrum feeding, and formula or cow milk intake during infancy have any relationship with the development of MS, which type of MS would be influenced further, and if breastfeeding has any effect on the age of MS onset. Materials and Methods: 100 MS patients and 100 healthy controls took part in this study. Male to female ratio was similar in both groups. Demographic characteristics and history of breastfeeding were collected via a questionnaire. Results: The mean duration of breastfeeding was considerably lower in some MS patients who had onset of the disease before or at the age of 30 compared to those with onset after 30 years (15.2 + 10.2 versus 19.5 + 11.0 months, P = 0.09). Breastfeeding with a duration of more than 11 months was more frequent in the latter group (83% versus 60%, P = 0.044). Patients with age-onset before or at 30 also revealed a higher rate of feeding with formula or cow milk (56.5% versus 33% and P = 0.063). More frequent feeding with formula or cow milk among MS patients compared to healthy controls (51% versus 31%, P=0.006) was observed. Conclusion: Formula or cow milk consumption during infancy may be a considerable risk factor for developing MS besides other etiologic factors.